Efficacy and safety of anlotinib in the treatment of brain metastases from non-small cell lung cancer: a systematic review and meta-analysis - Fang, Chunyue; Yue, Congbo; Wu, Junzhu; Yao, Tianliang; Wen, Jin; Dai, Wei; Yang, Qionghui; Chen, Ruixiang; Li, Qinghuan; Zhong, Yuanyuan (Frontiers in Pharmacology, 2025)
BackgroundThe presence of brain metastases is a significant factor contributing to the failure of lung cancer therapies. This study aims to systematically assess the efficacy and safety of anlotinib in the treatment of brain metastases resulting from non-small cell lung cancer (NSCLC).MethodsA comprehensive literature search was conducted across multiple databases, including PubMed, EMBASE, Cochrane Library, Web of Science, CNKI, Wan fang, and VIP databases. This search encompassed the period from the establishment of the databases up until November 2024. The Cochrane risk of bias tool was employed to assess the quality of the randomized controlled trials (RCTs) included in the study, while the quality of the cohort studies was evaluated using the Newcastle-Ottawa Scale (NOS) score. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was used to evaluate the quality of evidence. The meta-analysis was conducted using the RevMan 5.3 software.ResultsA total of 18 studies (9 RCTs and 9 retrospective cohort studies; n = 1,480) were included in the analysis. The results demonstrated that, compared to the control group, anlotinib significantly prolonged intracranial progression-free survival (IPFS)[3 studies; HR = 0.52, 95% CI (0.36–0.75), P = 0.0004, I2 = 0%, fixed-effect model] and improved overall survival (OS) [3 studies; HR = 0.69, 95% CI (0.54–0.88), P = 0.0003, I2 = 0%, fixed-effect model]. Furthermore, anlotinib increased the objective response rate (ORR) [15 studies; RR = 1.55, 95% CI (1.30–1.84), P < 0.00001, I2 = 58%, random-effects model] and disease control rate (DCR) [13 studies; RR = 1.33, 95% CI (1.23–1.44), P < 0.00001, I2 = 29%, fixed-effect model]. Regarding safety outcomes, the anlotinib group showed a significantly reduced risk of nausea-vomiting [7 studies; RR = 0.52, 95% CI (0.29–0.92), P = 0.02, I2 = 0%, fixed-effect model], while no significant differences were observed in other adverse reactions.ConclusionAnlotinib may prolong IPFS and OS in patients with brain metastases from NSCLC, and may improve ORR and DCR. In terms of safety, may reduce the risk of nausea-vomiting. The risk of bias in some of the included studies was unclear. The quality of OS and DCR was moderate, while that of IPFS, ORR and nausea-vomiting was low.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025632195, identifier [CRD42025632195].